2022
DOI: 10.1097/ju.0000000000002931
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactate Dehydrogenase in Identifying Relapse for Patients With Stage I Testicular Cancer on Surveillance

Abstract: Purpose:Tumor markers alpha-fetoprotein, human chorionic gonadotropin, and lactate dehydrogenase assume a key role in the management of testicular germ cell tumors. While alpha-fetoprotein and human chorionic gonadotropin have modest sensitivity and specificity for germ cell tumors, lactate dehydrogenase has weak sensitivity and specificity. We explored the utility of lactate dehydrogenase in identifying relapse among stage I seminomatous and nonseminomatous germ cell tumors on surveillance.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…[27] on the reliability of STM in CS1 NSGCT surveillance found that STM were only elevated in 28%–75% of patients at the time of relapse and STM were only the sole indicator of relapse in 4%–39% of cases. Similarly, the utility of LDH has been questioned in CS1 NSGCT surveillance [8,51]. A recently published study demonstrated LDH never was the sole indicator of relapse in 176 relapsing patients with NSGCT and LDH was falsely elevated in 75% of non‐relapsing patients with NSGCT on surveillance [8].…”
Section: Follow Up In Nsgctmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] on the reliability of STM in CS1 NSGCT surveillance found that STM were only elevated in 28%–75% of patients at the time of relapse and STM were only the sole indicator of relapse in 4%–39% of cases. Similarly, the utility of LDH has been questioned in CS1 NSGCT surveillance [8,51]. A recently published study demonstrated LDH never was the sole indicator of relapse in 176 relapsing patients with NSGCT and LDH was falsely elevated in 75% of non‐relapsing patients with NSGCT on surveillance [8].…”
Section: Follow Up In Nsgctmentioning
confidence: 99%
“…A recently published study showed that only 28% of relapsing patients with CS1 seminoma on surveillance had an elevated LDH and was falsely elevated in 60% non-relapsing patients. LDH was never the sole indicator of relapse, which raises questions on the utility of LDH as a STM in seminoma surveillance [8].…”
Section: Serum Tumour Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH serves as a marker that lacks specificity, although it possesses an autonomous prognostic significance in males afflicted with advanced TC. Literature has documented that LDH accurately mirrors both the rate of tumor expansion and the extent of tumor mass 101 . Elevated concentrations of serum lactate dehydrogenase (LDH) have been documented in roughly 80% of advanced seminomas and approximately 60% of non‐seminomas 101 .…”
Section: Introductionmentioning
confidence: 99%
“…Literature has documented that LDH accurately mirrors both the rate of tumor expansion and the extent of tumor mass 101 . Elevated concentrations of serum lactate dehydrogenase (LDH) have been documented in roughly 80% of advanced seminomas and approximately 60% of non‐seminomas 101 . While AFP, HCG, and LDH are frequently employed serum markers in the management of TC, their specificity is limited and their detection rate in men with TC is only approximately 60% 102 .…”
Section: Introductionmentioning
confidence: 99%